2015
DOI: 10.1038/modpathol.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

The neuroblastoma and ganglion components of nodular ganglioneuroblastoma are genetically similar: evidence against separate clonal origins

Abstract: Nodular ganglioneuroblastoma is characterized by a macroscopic nodule of neuroblastoma within a ganglioneuromatous component. These two components have been considered to originate from separate clones, with the neuroblastoma clone accounting for the clinical behavior of nodular ganglioneuroblastoma. In order to investigate the clonal origin of the cellular components (neuroblasts, ganglion cells, and Schwann cells) of nodular ganglioneuroblastoma, paraffin-embedded tumor samples from eight cases were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…FISH analysis for MYCN copy number, chromosome 1p loss and chromosome 17q gain was performed as previously described . Briefly, spectrum orange‐ or spectrum green‐labeled bacterial artificial chromosomes (BACs) DNA were acquired from the Applied Centre for Genomics, Toronto, Canada (http://www.tcag.ca/) and selected based on the UCSC genome browser (http://genome.ucsc.edu).…”
Section: Methodsmentioning
confidence: 99%
“…FISH analysis for MYCN copy number, chromosome 1p loss and chromosome 17q gain was performed as previously described . Briefly, spectrum orange‐ or spectrum green‐labeled bacterial artificial chromosomes (BACs) DNA were acquired from the Applied Centre for Genomics, Toronto, Canada (http://www.tcag.ca/) and selected based on the UCSC genome browser (http://genome.ucsc.edu).…”
Section: Methodsmentioning
confidence: 99%
“…When tested, 11q loss was also detected in the ganglioneuromatous component of the tumour, but not in Schwann cells. Altogether, the results obtained from using SNP arrays and FISH suggest that Schwann cells have a different origin and are not clonally related to the other compounds [133]. …”
Section: Introductionmentioning
confidence: 99%
“…Andrew et al reported that the 5-year survival probability of patients with GNB was approximately 88 % and that the prognosis of children with GNB was better than that of adolescents and adults with GNB [ 8 ]. In a survival analysis of 232 GNB patients, Paola Angelini et al reported that age was an independent prognostic risk factor for GNB [ 7 ]. Many studies have revealed that ageing increases the risk of cancer, which is possibly related to the accumulation of gene mutations throughout the life cycle [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…GNB primarily affects children – its incidence rate in this population is no more than 5 cases per million children – but it can also occur in adolescents and adults [ 5 ]. Age is an independent prognostic factor for GNB [ 6 , 7 ]. A retrospective study suggested that the 5-year survival rate of GNB patients was approximately 88 % [ 8 ].…”
Section: Introductionmentioning
confidence: 99%